Smallanthus macroscyphus: a new source of antidiabetic compounds - Serra Barcellona, Carolina (2013)
The aim of the present study was to analyze the in vivo hypoglycaemic effects of both decoction of Smallanthus macroscyphus leaves and pure crystalline polymatin A isolated from its leaves. Phytochemical analysis of the leaf decoction showed that its major constituents were caffeic, chlorogenic and three dicaffeoilquinic acids, together with the sesquiterpene lactone polymatin A. Oral glucose tolerance test in normal rats was performed to evaluate the hypoglycemic activity and to choose the minimum effective dose of the decoction and polymatin A. They have effective hypoglycemic activity at the minimum dose of 140 mg dry extract and 14 mg crystalline powder/kg body weight, respectively, and were selected for the following experiments. Oral administration of a single-dose of decoction produced a moderate lowering effect in fasting glycemia of normal rats, whereas polymatin A had no significant effect. We also assessed the effect of a single-dose on post-prandial blood glucose, resulting in an inhibition of the hyperglycemic peak after sucrose overload. Daily administration of decoction or polymatin A for 4 weeks produced an effective glycemic control in diabetic animals, with a decrease in urinary glucose excretion and a significant reduction in the HbA1c levels. Although there were no significant increases in plasma insulin levels, both treatments improved the fasting blood glucose/insulin ratio. In vivo acute toxicity studies were performed in adult Wistar rats. There were no deaths or signs of toxicity observed after oral administration of decoction or polymatin A at any dose level up to the highest dose tested (14.0 g /kg and 2.8 g /kg, respectively). The results presented here strongly support the notion that S. macroscyphus represents a new source of antidiabetic compounds that could help to manage diabetes more efficiently and safely.